Town- and Spatial Planners – Transformations of the Profession - Krau, Ingrid (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The profession of spatial planners started in Germany in 1968 with its first belated planning-department apart from town-planning education within architectural faculties, shaping its thinking in contrast to architectural-led town-planning. Regarding the career of 45 years of planner-education, we find fundamental transformations of the planners’ thinking, leading from a rather autonomous start-off apart from established planning, ending up in the acceptance of the predominance of self-regulating markets and governance structures. Led by incremental thinking and negotiation, spatial planners have separated themselves from physical planning as well as from planning-theory which could guideline their thinking, renouncing goal-led development and formal plans; on the other hand town planners have restricted themselves to informal physical plans with little power of implementation. Especially since the financial crisis after 2000 planning gives way to neoliberal arrangements, resulting in growing imbalance and fails in spatial development. So the demand of sovereign thinking to crosscounter this development is increasing. This leads to a challenge for planning-departments to reconsider their educational ambitions and to enlarge knowledge and skills by transdisciplinary cooperation to develop answers to the unsolved questions beyond the old separation of disciplines.
Keywords: Planning education; Urban design thinking; Incrementalism; Governance; Neoliberalism